2017
DOI: 10.1038/emm.2017.180
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial folliculin is involved in airway inflammation in workers exposed to toluene diisocyanate

Abstract: Toluene diisocyanate (TDI) exposure can directly activate and damage airway epithelium. Folliculin (FLCN) is a protein expressed by human airway epithelial cells (HAECs) to maintain airway epithelial integrity and survival. This study investigated the involvement of FLCN in the pathogenesis of TDI-induced occupational asthma (OA). Enzyme-linked immunosorbent assay was used to measure serum levels of FLCN in TDI-exposed subjects (93 TDI-OA patients and 119 asymptomatic exposed controls (AEC)), 200 non-occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…however, there is only 1 report showing the association of FLCN in TDI-induced occupational asthma. 18 In the present study, the asthmatic patients with highFLCN were associated with airway hyperresponsiveness to MCh. However, among the patients with AERD, highFLCN was not directly associated with the features of AERD such as severe asthma, airway hyperresponsiveness and CRS/NPs, indicating that serum FLCN may not be directly associated with key clinical features, but contribute to aggravating the severity of airway inflammation in AERD, as AERD subjects with highFLCN had a higher serum TGF-β1 level.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…however, there is only 1 report showing the association of FLCN in TDI-induced occupational asthma. 18 In the present study, the asthmatic patients with highFLCN were associated with airway hyperresponsiveness to MCh. However, among the patients with AERD, highFLCN was not directly associated with the features of AERD such as severe asthma, airway hyperresponsiveness and CRS/NPs, indicating that serum FLCN may not be directly associated with key clinical features, but contribute to aggravating the severity of airway inflammation in AERD, as AERD subjects with highFLCN had a higher serum TGF-β1 level.…”
Section: Discussionmentioning
confidence: 46%
“…Previous work has generally focused on the role of FLCN in the Birt‐Hogg‐Dubé syndrome and pneumothorax in adults,; however, there is only 1 report showing the association of FLCN in TDI‐induced occupational asthma . In the present study, the asthmatic patients with highFLCN were associated with airway hyperresponsiveness to MCh.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…A study by Pham et al . demonstrated that inflammatory conditions such as asthma and chemical exposure induced FLCN production in human airway epithelial cells . They suggested that FLCN may have a protective function in pneumocytes, and that dysregulated FLCN may affect cellular homeostasis, contributing to lung disease.…”
Section: Possible Mechanism Of Cyst Formationmentioning
confidence: 99%
“…Additionally, folliculin is a protein derived from airway epithelial cells. Its production is increased by epithelial cell activation in asthmatic patients [9].…”
Section: Introductionmentioning
confidence: 99%